ChemInform Abstract: Arylcalixarenyl Phosphines in Palladium‐Catalyzed Suzuki—Miyaura Cross‐Coupling Reactions. Issue 34 (4th August 2016) - Elaieb, Fethi; Hedhli, Ahmed; Semeril, David; Matt, Dominique
Abstract: Calix[4]arene (CAX) is an efficient ligand for Pd‐catalyzed Miyaura cross‐coupling reactions of sterically hindered aryl chlorides and boronic acids.